Investigation of health condition of small indigenous species Channa punctatus from Sherpur and Mymensingh areas - Ahmed, Gias Uddin; Khatun, Sahara; Rahman, Md Mamunur (Asian Journal of Medical and Biological Research, 2016)
Investigation on the health condition of small indigenous fish, Channa punctatus was carried out through clinical and histological observation from Jailka beel of Sherpur sadar, Sherpur district and Kailla beel of Ishargonj upazila, Mymensingh district for a period of six months from October 2014 to March 2015. Water quality parameters like water temperature, pH, dissolved oxygen, ammonia, total hardness, alkalinity and nitrate were recorded. Water temperature and total hardness were found at unfavorable level for fish in December and January. Clinical examinations of the fish were also carried out for any kind of abnormalities at monthly intervals. Clinically, it was observed that fish was affected with numerous red spots and patches in lateral and ventral regions, large deep whitish ulcers reached up to deep ulcers especially in December and January in both the beels. Samples of skin, muscle, gill, liver and kidney were collected and processed for histological observations. Major pathology in the skin and muscle were epidermis separated from dermis, presence of fungal granuloma, vacuums, hemorrhage and necrosis. Loss of primary and secondary gill lamellae, hypertrophy and primary gill lamellae separated, necrosis and hemorrhage were found in the gill. Large vacuums, necrosis and hemorrhage were observed in liver and kidney. Among the affected fish organs, skin and muscle, gills were found to be more affected than those of the internal organs like liver and kidney. Overall, under the clinical and histopathological observations the fish were found to be more affected in December and January. Whereas, in the months of February and March, the pathological condition of fish gradually healed up to normal except few vacuums and hemorrhage. Under histopathological observations, fish of Jailka beel were more affected than the fish of Kailla beel. In clinical and histopathological observation C. punctatus was more affected due to EUS. Asian J. Med. Biol. Res. September 2016, 2(3): 464-470